Eight-year-delayed Diaphragmatic Hernia due to a Blunt Trauma: A Case Report - Tamburian, Christha Z.; Sukanto, Wega; Pontoh, Pramijaya E. (Universitas Sam Ratulangi, 2026)
Abstract: Traumatic diaphragmatic rupture is an uncommon but potentially life-threatening injury, typically caused by blunt or penetrating thoraco-abdominal trauma. While most cases are identified in the acute phase, delayed presentations may occur years after the initial injury, often with nonspecific symptoms. Recognition requires a high index of suspicion to avoid morbidity associated with late diagnosis. We reported a 33-year-old male with a history of blunt chest trauma sustained eight years prior, who presented with incidental findings of a left diaphragmatic hernia. The patient was asymptomatic aside from decreased breath sounds on auscultation. Chest computed tomography revealed herniation of abdominal viscera, including the stomach, colon, omentum, and spleen, into the left thoracic cavity. Surgical management consisted of left posterolateral thoracotomy with reduction of herniated contents, adhesiolysis via laparotomy, and primary repair of a 10 × 5 cm diaphragmatic defect using interrupted non-absorbable sutures. Postoperatively, the patient recovered well with resolution of lung expansion and no evidence of recurrence on follow-up imaging. In conclusion, delayed diaphragmatic hernia following blunt trauma is a rare clinical entity that may remain silent for years before diagnosis. Thorough history-taking, clinical suspicion, and advanced imaging are critical in identifying such cases. Early surgical intervention remains the cornerstone of management, aiming to restore diaphragmatic integrity, prevent visceral complications, and optimize respiratory function. Keywords: delayed diaphragmatic hernia; blunt trauma; thoracotomy; diaphragmatic rupture